Diagnosis of obesity and evaluation of the risk of premature death (ABSI) based on body mass index and visceral fat area - Maroš Bihari; Marta Habánová; Kristína Jančichová; Martina Gažarová (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. Body mass index (BMI) is the most commonly used parameter for identifying obesity. However, it is a tool that can distort the diagnosis as misdiagnose. Objective. The aim of the study was to evaluate the BMI and visceral fat area (VFA) and to determine the presence of obesity in a group of young people and to assess their suitability for use together with other parameters indicating excessive body fat and increased risk of non-communicable disease and premature death. Material and Methods. The study group consisted of 339 university students. We used InBody 720 for diagnosis body composition. The following body composition parameters were measured - BMI, waist circumference (WC), fat-free mass (FFM), VFA, percentage of body fat (PBF). Results. The BMI values by gender indicate overweight in the male group compared to females (25.2 ± 3.1 and 22.2 ± 3.4 kg.m-2, respectively; p<0.001). Women had higher values of VFA than men (70.1 ± 26.4 and 56.2 ± 28.3 cm2, respectively; p<0.001). Although the group of men had an increased average BMI, which allows us to talk about overweight, the risk of premature death was low. In the case of the male group, a high proportion of fat-free mass had a major impact on BMI. Lower values of fat parameters also contributed to the low risk of premature death. We found a nonlinear relationship in the BMI assessment in terms of premature risk of death. Higher values of the premature death risk were found in the subgroups of underweight and obesity. In the case of the VFA and ABSI relationship a linear increase in the curve and the risk of premature death was observed. Conclusions. In order to evaluate the presence of overweight or obesity it is necessary to use not only BMI but other diagnostic elements for this purpose. The components of the body composition need to be evaluated comprehensively. Evidence of this is the risk of premature death, where optimal BMI values may pose an increased risk and vice versa.